Do wrist orthoses cause compensatory elbow and shoulder movements when performing drinking and hammering tasks?. Issue 1 (3rd April 2018) - Stofer, Virginia P.; McLean, Scott; Smith, Jimmy
Abstract : Purpose: Wrist orthoses are used by occupational therapists to decrease pain, support weak muscles and protect tissues during healing. However, use of wrist orthoses has been observed to produce compensatory movements in other upper extremity joints. This paper aims to determine whether wearing wrist orthoses produced compensatory movements of the elbow in addition to the shoulder when performing drinking and hammering tasks. Design/methodology/approach: Two twin-axis electrogoniometers were positioned on the elbow and shoulder to track joint movement. The four conditions were drink with orthosis, hammer with orthosis, drink without orthosis and hammer without orthosis. Joint movement was defined as total angular excursion of the joint throughout the performance of the task. Separate 2 × 2 (joint × orthosis) repeated measures analyzes of variance (ANOVA) were used to evaluate differences in joint excursion of the elbow and shoulder joints between orthosis conditions for each task. Findings: Wearing a wrist orthosis did not change the amount of joint excursion compared to not wearing an orthosis during the drinking and hammering tasks. Originality/value: Findings suggest that wrist orthoses do not result in statistically significant changes in elbow and shoulder joint movements during simulated drinking and hammering tasks.